Polymorphism in IL-6(-174 G/C) Gene in Scabietic Patients (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background : Scabies (Sarcoptes scabiei var. hominis) is one of the parasitic diseases that is often ignored. It results in problems that trigger an allergic and inflammatory immunological response. Cytokines are crucial to the development of disease and its pathophysiology. This investigation looked at how scabies risk and a variation in the gene IL-6 affected IL-6 production.Materials and Methods : The goal of the current investigation was to determine the level of IL-6 by ELISA and its linked with IL-6(-174 G/C) polymorphisms in 60 scabietic patients and 30 healthy individuals.Results : In contrast, the IL-6(-174 G/C) CC genotype and C allele carrier frequencies were highly significant (P0.05) in the patients who had their first infestation. The results showed a significant increase (P0.05) in the IL-6(-174 G/C) GG genotype and G allele in the re-infestation group of patients compared to the healthy group. According to IL-6 genetic variations, low serum levels were connected with the CC genotype.Conclusion : IL-6(-174 G/C) Scabies susceptibility and polymorphism were related, providing evidence for the hereditary basis of the illness